Interactive air pollution mapping tool for experts - Vital, Duarte Vaz Correia (2020)
Air pollution, especially in city areas, has been a big concern for decades now. Real-time air quality monitoring stations have become the standard in measuring air pollution for their accuracy and reliability. As a result, extensive pollution maps are nowadays created mainly using information from these stations. Two types of pollution mapping solutions are most prominent: maps that display sparse monitoring stations' locations and respective gathered time varying air pollution data; and estimated dense pollution heatmaps resulting from a combination of air quality sensor data and additional data, such as meteorological and traffic information. In alternative, this dissertation proposes the use of expert knowledge as a complementary means for generating air quality maps. The goal is to allow experts to express their knowledge about how air pollution is emitted and diffused as a function of the presence of key topological elements, such as buildings and roads. To this end, a tool was developed and validated with a set of 30 participants. The obtained results confirm the tool's usability and highlight key future research directions to bring the proposed concept closer to a fully functional solution.